2003
DOI: 10.1063/1.1581362
|View full text |Cite
|
Sign up to set email alerts
|

A computerized Langmuir probe system

Abstract: For low pressure plasmas it is important to record entire single or double Langmuir probe characteristics accurately. For plasmas with a depleted high energy tail, the accuracy of the recorded ion current plays a critical role in determining the electron temperature. Even for high density Maxwellian distributions, it is necessary to accurately model the ion current to obtain the correct electron density. Since the electron and ion current saturation values are, at best, orders of magnitude apart, a single curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In this study the design of data acquisition system is presented, which ensures accurate measurements of the current-voltage (I-V) single probe characteristics without current sensing resistor. Current sensing resistor is the conventional and simplest method of measurements [9,[26][27][28], but although simple to implement, there are certain problems with this approach. If the resistor is floating, a differential voltage signal has to be converted additionally before it is measured by a grounded oscilloscope.…”
Section: Introductionmentioning
confidence: 99%
“…In this study the design of data acquisition system is presented, which ensures accurate measurements of the current-voltage (I-V) single probe characteristics without current sensing resistor. Current sensing resistor is the conventional and simplest method of measurements [9,[26][27][28], but although simple to implement, there are certain problems with this approach. If the resistor is floating, a differential voltage signal has to be converted additionally before it is measured by a grounded oscilloscope.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed plasma and pulsed ion beam phenomena can be investigated using the Langmuir probe [10][11][12] and Faraday cup diagnostics. These efficient diagnostic methods have been used to study the change of plasma and beam parameters in the hydrogen ECR plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3]. One of these techniques is the use of the Langmuir double probe [19][20][21][22][23][24], as well as the use of the spectrum emitted from the plasma by using it to calculate the parameters of the plasma [25]. Salman et al [26] changed the distance between the double probe and studied the effect of this change on the I-V characteristic curve Ghasemi et al [27] found the electron temperature and electron density practically and in a simulated manner using the Langmuir double probe and they calculated the frequency of the argon plasma which was the highest and the electron temperature in the hydrogen plasma was the highest.…”
Section: Introductionmentioning
confidence: 99%